2017
DOI: 10.1016/j.resconrec.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Regional disparities in the Chinese economy. An emergy evaluation of provincial international trade

Abstract: Due to different resource endowment, geographical features, culture and population size, different regions are facing different challenges and therefore need to adopt different strategies toward sustainable development. China's Eastern, Central and Western provinces are taking different policies on international trade in order to boost their economy. This paper tries to investigate what extent a province receives a trade advantage and the corresponding environmental resource flows by employing an emergy accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 36 publications
0
13
0
1
Order By: Relevance
“…China has faced serious challenges such as resource depletion and environmental degradation [8]. Although the different regions in China are facing various challenges due to different resource endowment, geographical features, economic level and population sizes [9], the common problem of China is the low level of ecological construction including poor environmental protection [10]. Therefore, the government must develop a green economy and increase investment on environmental protection in the future.…”
Section: Introductionmentioning
confidence: 99%
“…China has faced serious challenges such as resource depletion and environmental degradation [8]. Although the different regions in China are facing various challenges due to different resource endowment, geographical features, economic level and population sizes [9], the common problem of China is the low level of ecological construction including poor environmental protection [10]. Therefore, the government must develop a green economy and increase investment on environmental protection in the future.…”
Section: Introductionmentioning
confidence: 99%
“…); for metallurgical complex -Italy, for leather products and shoes industry -Turkey, for mechanical engineering -Ukraine. 4 Thereby, the goal of effective import substitution in the Rostov region is the advanced development of some industries, which are selected taking into account national priorities, specialization and resource potential of regional economy. These industries are following: machine-tool construction (import dependence level is 90 %); radio and electronic industry (82 %); light industry (72.5 %); oil and gas mechanical engineering (24 %); avia- tion industry (helicopter construction) (24 %); power engineering industries (19.7 %); chemical industry (9.7 %).…”
Section: The Results Of An Assessment Of the Impact Of Import Substitmentioning
confidence: 99%
“…The paper demonstrates that various regions of national economy, taking into account their realities, take different foreign trade courses for the purpose of economic development. [4]. But there are not enough research on how import substitution in a region improves the positioning of its economy in a system of international economic relations.…”
Section: Theoretical Framework For the Study Of Import Substitution Amentioning
confidence: 99%
“…Ran et al (2007) indicate that, although FDI still has a positive effect on China's economy, this investment leads to the widening of regional disparity and, as a result, to the emergence of "backward" regions. Tian et al (2017) study peculiarities of the impact of international trade on economic development of Chinese provinces. It is found that foreign trade has the positive influence on the country's regions, but its effect is not equal for all provinces.…”
Section: Discussionmentioning
confidence: 99%